2015
DOI: 10.1111/radm.12146
|View full text |Cite
|
Sign up to set email alerts
|

Towards an attention‐based view of technology decisions

Abstract: The importance of technology decisions is widely acknowledged in both research and practice. However, we know little about how companies structure technology decisions from an organizational point of view and how attention is distributed in the course of the decision process in order to identify, process, and transfer information between the organizational units involved. Using the attention‐based view of the firm and 14 qualitative case studies, we present five approaches for organizing technology decisions: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 53 publications
1
23
0
3
Order By: Relevance
“…Finally, the analysis offers new insights regarding the effects of timing in ideation processes. Recent studies on ideation (Chen et al , 2020; Palmie et al , 2015) have suggested that idea success depends on exposure. Increased exposure can result from increased attention when an idea does not surface at the same time as other ideas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the analysis offers new insights regarding the effects of timing in ideation processes. Recent studies on ideation (Chen et al , 2020; Palmie et al , 2015) have suggested that idea success depends on exposure. Increased exposure can result from increased attention when an idea does not surface at the same time as other ideas.…”
Section: Discussionmentioning
confidence: 99%
“…The literature shows that the temporal dimensions matter and can significantly affect attention allocation in organizations (Cummings and Haas, 2012). Time allocation is, indeed, of quintessential importance to explain patterns of competition as well as variation in attention dynamics where employees are allocating time to novel ideas (Palmie et al , 2015).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…The evolutionary theory of firms is an offshoot of the behavioral theory of firms (Cyert and March 1963) whose family comprises some further theories such as the attentionbased view. The attention-based view has generated useful insights in both the MNE and the innovation literatures (Bouquet and Birkinshaw 2008;Palmié et al 2015). We thus believe that future research can substantially advance our understanding of innovationrelated phenomena, multinational organisations, and SME management by applying one of these theories.…”
Section: Limitations and Paths For Future Researchmentioning
confidence: 85%
“…We suggest an integrated approach, which involves all IP stakeholders, particularly external patent attorneys. As firms can benefit from including more stakeholders in highly important decisions (Palmié, Lingens and Gassmann 2016) and can improve their innovative and financial performance by interacting with different suppliers (Garcia Martinez et al, 2014), we argue that firms can improve the IP performance by interacting with external patent attorneys. Thus, filing of patents should be coordinated and aligned with all IP actors in order to achieve strategic goals, leverage the best combination of external and internal capabilities, and avoid undesirable or counter effects.…”
Section: Conclusion and Managerial Implicationsmentioning
confidence: 99%